Effect of immunization of rohu Labeo rohita with inactivated germinated zoospores in providing protection against Aphanomyces invadans. Issue 78 (July 2018) - Pradhan, Pravata K.; Sood, Neeraj; Yadav, Manoj K.; Arya, Pooja; Chaudhary, Dharmendra K.; Kumar, Uday; Kumar, Chandra Bhushan; Swaminathan, T.R.; Rathore, Gaurav
Abstract: Infection with Aphanomyces invadans is one of the most destructive diseases of freshwater fishes. Indian major carps, the dominant cultured species in the Indian sub-continent are highly susceptible to this disease. Till date, there is no effective treatment for control of this disease and immunization can be one of the strategies to reduce disease-related losses. In the present study, inactivated germinated zoospores of A. invadans were evaluated as antigen in conjunction with and without adjuvant Montanide™ ISA 763 A VG, for assessing their efficacy in rendering protection against A. invadans infection. For the experiment, rohu Labeo rohita, (n = 160, 74 ± 12 g) were divided into 4 groups (C, A, G and GA) with 40 fish in each group. The fish in groups i.e., C, A, G and GA were injected intraperitoneally with PBS, adjuvant emulsified with PBS, inactivated germinated zoospores, and inactivated germinated zoospores emulsified with adjuvant, respectively. After 21 days of immunization, the fish were given a booster dose as above. After 7 days of the booster dose, the fish were challenged with zoospores of A. invadans to determine the relative percent survival (RPS). The results revealed that all the fish in C, A and G group succumbed to infection (0% RPS), although there was delayed mortality in fish from A and G groups in comparison to the C group. However, the fish in GA group showed significantly higher (P < 0.05) protection (66.7% RPS). In addition, following booster immunization (before challenge), the antibody level in the GA group was significantly higher (P < 0.05) than the control group. In western blotting, sera from G and GA groups showed reactivity with peptides of about 54 KDa. Following challenge (on 14th day), the antibody level as well as total antiprotease activity in fish of all the groups was significantly decreased in comparison to pre-challenge, except fish in GA group not exhibiting any gross lesions. In addition, sera of surviving fish of GA group showed significant inhibition of germination of zoospores and germlings growth in comparison to other groups (P < 0.05). Further, histopathological examination of the muscle tissue revealed that, in fish of GA group without any gross lesions, there were well developed granulomas and extensive mononuclear cell infiltration restricted to the site of injection, whereas in other groups, there was extensive myonecrosis with proliferating hyphae. These preliminary findings indicate that inactivated germinated zoospores of A. invadans in combination with adjuvant could stimulate good immune response and confer remarkable protection in rohu. Graphical abstract: Image 1 Highlights: Infection with Aphanomyces invadans is one of the most destructive diseases of freshwater fishes. Inactivated germinated zoospores of A. invadans were evaluated as antigen for immunization. The antigen along with adjuvant Montanide rendered significant protection against infection with A. invadans. The protection was positively correlated with specific antibody level and total antiprotease activity.